Implementasi Pemikiran Afzalur Rahman tentang Produksi Berbasis Konsep Al-‘Adl dalam Meningkatkan Kepuasan Konsumen. - M. Wahyuddin Abdullah; Faiz Almath; Rahmawati Muin (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2020)
This research aims to determine implementation of Afzalur Rahman’s idea based the al-‘adl concept to improving consumer satisfaction. This research is a qualitative research with a phenomenology approach at CV Sinar Permai in Konawe Southeast Sulawesi. The results showed that production mechanisms in the company’s involve the process of material handling, skidding, and transferring. Implementation of production based ‘adl concept has been applied with the values of fairness in all production activities, start from the provision of raw materials, production processes, including use of manpower in production activities. The implementation of production to improving customer satisfaction is to provide assurance of security, comfort, quality of service, and ensure the production of products received by consumers.